Gaya Kepemimpinan dan Kinerja Pegawai: Studi Kasus di Dinas Pendidikan Kabupaten Tanggamus - Pramono, Eko; Hadjar Aswad, Fatqul; Siswoyo (Manajemen Pendidikan, 2025)
Employee performance is a key factor in the effectiveness of government organizations, especially in the regional education sector. Effective leadership can affect employee motivation, productivity, and job satisfaction. This study aims to analyze the influence of leadership style on employee performance at the Tanggamus Regency Education Office and identify the most effective leadership strategies in improving the quality of employee work. This study uses a qualitative descriptive approach with a case study method. Data was collected through in-depth interviews, direct observations, and documentation analysis, with the main informants consisting of heads of agencies, heads of fields, and employees with various levels of position. Data analysis was carried out using data reduction techniques, data presentation, and conclusion drawing as proposed by Miles and Huberman (1994). The results of the study show that transformational leadership styles are more effective in improving employee motivation and performance compared to authoritarian or transactional leadership styles. Leaders who are open to innovation, provide emotional support, and implement effective communication are able to create a more productive and harmonious work environment. However, the study also found that leadership effectiveness is greatly influenced by external factors such as national policies, incentive systems, and the availability of work facilities. The implications of this study show that strengthening the leadership system in the local government sector needs to be accompanied by leadership training programs, incentive system reform, and the use of technology in education management. This study contributes to the development of leadership theory in the context of public organizations and provides recommendations for policymakers in improving the effectiveness of leadership in the regional education sector.